A curious case of cholestasis: oral terbinafine associated with cholestatic jaundice and subsequent erythema nodosum. (5th December 2014) - Kumar, Kartik; Gill, Anna; Shafei, Rachelle; Wright, Janine L
Abstract : Terbinafine is a commonly prescribed antifungal agent used in the treatment oftrichophytic onychomycosis and chronic cutaneous mycosis that are resistant to other treatments. This case report highlights a rarely documented but important adverse hepatic reaction that was caused by the use of oral terbinafine. A woman in her thirties presented with a 3-week history of jaundice, malaise, itching, nausea, decreased appetite, weight loss, dark orange urine and intermittent non-radiating epigastric pain. She had recently finished a 3-week course of oral terbinafine for a fungal nail infection. Liver biopsy findings were consistent with chronic active hepatitis secondary to a drug reaction. A few days after initial presentation, the patient developed erythema nodosum. Delayed development of erythema nodosum secondary to terbinafine could not be excluded.